Practice and awareness of salat obligation during hospital admission among female Muslim patients in Obstetrics & Gynaecology - Yusof, Nurul Mutmainnah; Abdul Aziz, Fatimah; Mustafa, Kamarul Bahyah; Awang, Mokhtar; Abdullah, Abdul Rahman (IIUM Press, International Islamic University Malaysia, 2018)
The study was a simple random sampling cross-sectional survey conducted among Muslim female in-patients in Obstetrics and Gynecology, aimed at measuring the prevalence of obligatory salat performed, and to identify the factors associated with non-compliance, as well as offering solutions in an effort to assist them in performing salat. Of the 100 patients recruited, only 36% performed the five times a day obligatory salat, 38% did not performed salat at all and 26% performed salat only occasionally. There was a significant difference in salat performance for those with different awareness and adherence to salat obligation pre-admission, different basic knowledge on salat during illness, and different supportive surroundings in the ward. No association noted between patient’s physical disabilities to salat performance. In conclusion, instilling basic knowledge of salat to our patients is important in improving their salat performance. Guidance from ward staff, improvement of salat facilities and patient’s education on salat during illness may improve future commitment to salat.